3 Lessons from Hyperinflationary Periods - Mark Bergen; Thomas Bergen; Daniel Levy; Rose Semenov (Harvard Business Review, 2022)
Inflation is painful, for firms, customers, employees, and society. But careful study of periods of hyperinflation point to ways that firms can adapt. In particular, companies need to think about how to change prices regularly and cheaply — because constant price changes can ultimately be very, very expensive. And they should consider how to communicate those price changes to customers. Providing clarity and predictability can increase consumer trust and help firms in the long run.
Keywords: E31; L16; M30; 330; Inflation; Hyperinflation; Pricing; Price Setting; Price Adjustment; Menu Cost; Cost of Price Adjustment; Implicit Contract; Long Term Relationship